2023
DOI: 10.1101/2023.03.13.532398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory dyadic interactions through the ‘eye’ of the social brain: How visual is the posterior STS interaction region?

Abstract: Human interactions contain potent social cues that not only meet the eye but also the ear. Although research has identified a region in the posterior superior temporal sulcus as being particularly sensitive to visually presented social interactions (SI-pSTS), its response to auditory interactions has not been tested. Here, we used fMRI to explore brain response to auditory interactions, with a focus on temporal regions known to be important in auditory processing and social interaction perception. In Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 90 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Thus, we could have expected to find that the difference of performance in processing intact versus scrambled conversations would be higher for dialogues than monologues. Here, previous attempts in finding analogous effect in the brain has been so far unconclusive (Landsiedel & Koldewyn, 2023; Olson et al, 2023), so this interaction, if it exists, has yet to be found. Still, in the current study we found the lowest RTs in processing intact dialogues as compared to every other condition in some experiments.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, we could have expected to find that the difference of performance in processing intact versus scrambled conversations would be higher for dialogues than monologues. Here, previous attempts in finding analogous effect in the brain has been so far unconclusive (Landsiedel & Koldewyn, 2023; Olson et al, 2023), so this interaction, if it exists, has yet to be found. Still, in the current study we found the lowest RTs in processing intact dialogues as compared to every other condition in some experiments.…”
Section: Discussionmentioning
confidence: 84%
“…The current findings on the representations of all three types of speech in STG, MTG, and the auditory cortex align well with the previous literature. The temporal cortex has been long implicated in speech comprehension (Crinion et al, 2003; Lindenberg and Scheef, 2007; Leonard and Chang, 2014) and listening to dialogs between people activates those areas (Landsiedel and Koldewyn, 2023; Santavirta et al, 2023). Intriguingly, we observed subtle differences in how each speaking feature was represented in the mentalization network.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 22, 2023. ; https://doi.org/10. 1101 Increased STS responses have been linked to a broad range of social cognitive processes, including perceiving biological motion, goal-directed action, social interaction, and social communication, extracting meaning from speech, mental state inference, and social norm processing (Pelphrey et al, 2004;Herrington et al, 2011;Deen et al, 2015;de Heer et al, 2017;Isik et al, 2017;Pegado et al, 2018;Lee Masson and Isik, 2021;Landsiedel and Koldewyn, 2023;McMahon et al, 2023). The STG and MTG have also been implicated in social cognitive processes, including social signal detection, the integration of verbal and nonverbal social cues, extracting social-affective meaning from observed touch, extracting meaning from speech, and perceiving social communication and antisocial behavior (Price, 2012;Sugiura et al, 2014;Holler et al, 2015;Lee Masson et al, 2018;Santavirta et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation